Analysis of Nitrogen and Phosphorus Spatiotemporal Variations and Their Influencing Factors in Sansha Bay - CAO Nuotong; LI Qingsheng; JIANG Jinlong (Haiyang Kaifa yu guanli)
Based on the investigation data of environmental factors in Sansha Bay in spring, summer and autumn of 2020, the spatiotemporal variation of environmental factors were analyzed, and the eutrophication level was evaluated based on eutrophication index method. Then the influencing factors of nitrogen and phosphorus were analyzed and pollution control suggestions were put forward. The results showed that nitrogen and phosphorus concentrations were higher in spring and autumn, but lower in summer. The spatial variation of DIN and DIP were different in different seasons. In spring and autumn, the content of DIN in Sansha Bay is higher than that in most other bays, while in summer it is lower than that in most other bays. The content of DIP in three season is higher than that in most other bays. The eutrophication level in Sansha Bay is severe eutrophication level, in which the eutrophication level is the highest in autumn, the second in spring, and the lowest in summer. The analysis of influencing factors of nitrogen and phosphorus showed that in spring and summer, land-based pollution was the main source of DIN, while DIP was influenced by land-based pollution, cage culture, and nutrient absorption by algae. In autumn, DIN and DIP were affected by a combination of land-based pollution and cage culture. In the end, we put forward some suggestions on pollution control, in order to provide reference for pollution control and environmental protection in Sansha Bay.